Pendampingan Akses Pasar Ekspor Specialty Coffee di Provinsi Lampung - Muslimin Muslimin; Mahatma Kufepaksi; Fajrin Satria Dwi Kesumah; Fiska Huzaimah (Pustaka Peradaban, 2025)
This community service activity aims to expand export market access for processed coffee, particularly specialty coffee, produced by middle-class export entrepreneurs in Lampung Province. Additionally, this activity endeavors to provide input on processed coffee export policy to enhance commodity added value, generate foreign exchange, and encourage investment in Lampung. The Community Based Development plus (CBD+) approach by Sambodo et al. (2023) was adapted, identifying four key factors for community development. The focus group discussion (FGD) method involved relevant stakeholders in Lampung. Results indicate that coffee is a strategic commodity for both Lampung and Indonesia, significantly contributing to the Gross Regional Domestic Product (GRDP) and Gross Domestic Product (GDP). The innovative efforts of Lampung's middle-class exporters to enter the Singaporean and Malaysian specialty coffee markets require affirmative policy support. In conclusion, middle-level specialty coffee exporters have transformative potential in driving community development and sustainable coffee production in Lampung through social innovation and ethical sustainable practices, contributing to the well-being of coffee-farming communities and their business success. Kegiatan pengabdian masyarakat ini bertujuan memperluas akses pasar ekspor kopi olahan, khususnya specialty coffee, produksi pengusaha ekspor kelas menengah Lampung. Selain itu, kegiatan ini berupaya memberikan masukan kebijakan ekspor kopi olahan untuk meningkatkan nilai tambah, devisa, dan investasi di Lampung. Pendekatan Community Based Development plus (CBD+) dari Sambodo et al. (2023) diadaptasi, mengidentifikasi empat faktor kunci pengembangan masyarakat. Metode forum diskusi kelompok (Focus Group Discussion) melibatkan pemangku kepentingan di Lampung. Hasil menunjukkan kopi sebagai komoditas strategis bagi Lampung dan Indonesia, berkontribusi signifikan pada PDRB dan PDB. Upaya inovatif eksportir kelas menengah Lampung memasuki pasar specialty coffee Singapura dan Malaysia memerlukan dukungan kebijakan afirmatif. Disimpulkan bahwa eksportir specialty coffee tingkat menengah berpotensi transformatif mendorong pembangunan masyarakat dan produksi kopi berkelanjutan di Lampung melalui inovasi sosial dan praktik etis berkelanjutan, berkontribusi pada kesejahteraan komunitas petani kopi dan keberhasilan bisnis mereka.